Decoherence: a closed-system approach - Fortin, Sebastian Ezequiel (2013)
The aim of this paper is to review a new perspective about decoherence, according to which formalisms originally devised to deal just with closed or open systems can be subsumed under a closed-system approach that generalizes the traditional account of the phenomenon. This new viewpoint dissolves certain conceptual difficulties of the orthodox open-system approach but, at the same time, shows that the openness of the quantum system is not the essential ingredient for decoherence, as commonly claimed. Moreover, when the behavior of a decoherent system is described from a closed-system perspective, the account of decoherence turns out to be more general than that supplied by the open-system approach, and the quantum-to-classical transition defines unequivocally the realm of classicality by identifying the observables with classical-like behavior.